The external environment: Implications for ILRI's systems research - Li Pun, H.H. (International Livestock Research Institute, 1999)
This presentation which is on the external environment and implications for ILRI's systems research outlines social trends, institutional trends, global trends, as well as environmental trends. It separately examines the institutional trends. Role of crop-animal systems in rural Development, and demand trends in the livestock sector (1993-2020) are also highlighted. Implications for ILRI are discussed and ILRI's purpose, instituional linkages, and ILRI's eco-regional coverage are illustrated.